2010
DOI: 10.1523/jneurosci.6174-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Input Drives Multiple Intracellular Information Streams in Somatosensory Cortex

Abstract: Stable perception arises from the interaction between sensory inputs and internal activity fluctuations in cortex. Here we analyzed how different types of activity contribute to cortical sensory processing at the cellular scale. We performed whole-cell recordings in the barrel cortex of anesthetized rats while applying ongoing whisker stimulation and measured the information conveyed about the time-varying stimulus by different types of input (membrane potential) and output (spiking) signals. We found that sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 85 publications
(145 reference statements)
2
14
0
Order By: Relevance
“…5 C ). This decrease in the late component is likely caused by reducing cortical recurrent activity triggered by the sensory input, which in some cases also induced UP states (Anderson et al 2000; Hasenstaub et al 2007; Reig and Sanchez-Vives 2007; Alenda et al 2010).
Figure 4.Whisker deflection activates M1 after the initial response in S1.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 C ). This decrease in the late component is likely caused by reducing cortical recurrent activity triggered by the sensory input, which in some cases also induced UP states (Anderson et al 2000; Hasenstaub et al 2007; Reig and Sanchez-Vives 2007; Alenda et al 2010).
Figure 4.Whisker deflection activates M1 after the initial response in S1.
…”
Section: Resultsmentioning
confidence: 99%
“…5). This delayed response component may reflect a stimulus-evoked UP state (Anderson et al 2000; Hasenstaub et al 2007; Reig and Sanchez-Vives 2007; Alenda et al 2010), which often originates in more frontal cortical regions (Massimini et al 2004; Ruiz-Mejias et al 2011). Another possibility might be the delayed protraction of the whiskers following the initial air puff.…”
Section: Discussionmentioning
confidence: 99%
“…Axon projections of L5 slender-tufted neurons have been shown to establish functional connections with L2/L3 pyramidal neurons (32,33). However, as spiking in supragranular layers does not increase significantly upon active whisking (20,41), the sensory information carried by these intracortical long range projections is likely within fine-scale synaptic activity (42). During active whisking, the membrane potential of L2 and L3 pyramidal neurons may therefore be locked to the phase of individual slender-tufted neurons (41).…”
Section: Contribution Of Slender-tufted Neurons To Cortical Signalingmentioning
confidence: 99%
“…Similar results were obtained from human BOLD fMRI data, which showed a robust and specific learning-related modulation of spontaneous activity (Lewis et al 2009). Along similar lines, Alenda et al (2010) showed that an ongoing stimulus can modulate spontaneous membrane potential fluctuations throughout its duration. As a result, it was suggested that the cortex behaves somewhat like a central pattern generator, a system with rich spontaneous dynamics that is strongly modulated by, and responsive to, sensory inputs (Yuste et al 2005).…”
Section: Introductionmentioning
confidence: 76%